The Effect Of Consumer Buying Interest On The Purchase Decision Of Thrift Goods In Minasa Maupa Main Market, Gowa District - Madulu, Jeni; Sakawati, Herlina; Syarifuddin, Syarifuddin; Rivai, Andi Muhammad (Pinisi Business Administration Review, 2024)
This study aims to determine the effect of consumer buying interest on the decision to purchase thrift goods at the Minasa Maupa Main market, Gowa Regency. This research uses quantitative research. Data collection techniques were carried out through observation, questionnaires, and documentation. The sample used in this study was 100 respondents. The data obtained from the research results were processed using data analysis and using the help of the SPSS software program version 24 which consisted of validity tests and reliability tests of research instruments, descriptive data analysis techniques and inferential statistical analysis. The results showed that the indicators used in each variable showed that consumer buying interest was in the very good category. For indicators on purchasing decision variables are in the very good category. Based on the results of the t test, the calculated t value is greater than the t table, so it can be concluded that there is an influence between consumer buying interest on purchasing decisions for thrift goods at the Minasa Maupa Main market, Gowa Regency.